Cleopatra VII, daughter of the Nile - Gregory, Kristiana (New York : Scholastic, 1999)
While her father is in hiding after attempts on his life, twelve-year-old Cleopatra records in her diary how she fears for her own safety and hopes to survive to become Queen of Egypt some day.
Keywords: Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Juvenile fiction; Cleopatra, -- Queen of Egypt, -- d. 30 B.C. -- Fiction; Diaries -- Fiction; Egypt -- History -- To 640 A.D. -- Juvenile fiction; Egypt -- History -- To 640 A.D. -- Fiction